Building a Sustainable University Campus in Turkey: The Case of Istanbul Sabahattin Zaim University - Mehmet Bulut (Universitas Diponegoro, 2021)
As defined by Brundtland (1987), sustainable development is that which seeks to meet the needs of the present generation without compromising the ability of future generations to meet their own needs. This requires however, a holistic approach to defining appropriate philosophies and more ethical yet creative solutions vis-a-vis climate change, poverty elimination, countering inequality, preserving earth and striving for prosperity. Educational institutions, and especially those of higher learning, have a major role to play in this domain. This paper sheds light on the share of responsibility taken at Istanbul Sabahattin Zaim University (IZU) towards sustainable development goals and world’s complex challenges, and most importantly, its best practices in the management of UI GreenMetric indicators. This study explores some of IZU's current approaches and strategies adopted in the context of Turkish Waqf based higher learning institutions, and particularly, the ways and means according to which IZU continues to manage core domains of sustainable development and green initiatives whether related to setting and infrastructure, energy and climate change, waste, water, transportation or education, in addition to its various contributions to make to education and training, research and application, disseminating of ethics of green, and strengthening of its broad yet inclusive community engagement and global partnership support and development. This research shows that IZU's investment in sustainability interestingly represents one of its foundational core ethical values disseminated, and that its broad-spectrum practices, strategies, policies and systems of operation and management are underpinned in its very cultural and historical fabric of planetary preservation and stewardship